Obturator Nerve Block Performed Blinded Versus by Ultrasound-guidence for Transurethral Resection of Bladder Tumors: A Randomized Controlled Trial - Yasar, Eylem; Uysal, Ali Ihsan; Akarken, Ilker; Altiparmak, Basak; Gumus Demirbilek, Semra (Urology Journal, 2024)
Purpose: The primary outcome of this study is to compare the success rates of ONB techniques performed either with ultrasound guidance or with the blind technique. The second outcome is to compare the incidences of perioperative bleeding and the presence of recurrent tumors in the control cystoscopy performed in the 3rd postoperative month in both groups. Materials and Methods: The study was conducted in the urology operating room of Mugla Sitki Kocman Training and Research Hospital between December 2019 and March 2023. A total of 122 patients were included in the study: 22 females with a mean age of 56.63 ± 12.99 years and 100 males with a mean age of 63.18 ± 8.00 years. In one group (group 1), ONB was performed under ultrasound guidance by the same anesthesiologist, and in another group (group 2), ONB was performed blindly based on anatomical signs by the same urologist. Results: Adductor muscle contraction was not observed in 53 patients (91.4%) in group 1 and in 49 patients (76.6%) in group 2 (p = 0.027). Conclusion: The success rate of ONB was higher when using an ultrasound-guided technique than when using a blind technique.